A performance evaluation and assessment scheme (PEAS) for improving the Philippine newborn screening program - David-Padilla, Carmencita; Basilio, Juanita A.; Therrell, Bradford L.
Newborn Screening in the Philippines began as a small pilot project in Manila in 1996 and has expanded to a nationwide program screening for 5 conditions today. Along the way, professional, political and public support has increased. As a result, a national law requiring the offering of screening to all newborns was put into place. The Department of Health (DOH) is actively providing follow-up support, and the National Institutes of Health - University of the Philippines Manila (NIH) provides laboratory and technical expertise. Expansion has evolved to the point that there are now two DOH accredited screening laboratories with further expansion anticipated. The Newborn Screening Reference Center at the NIH has partnered with the DOH to develop a performance evaluation and assessment scheme (PEAS). The Philippine PEAS is designed to monitor quality and improvements made in the regional DOH screening program. The Philippine PEAS was developed building on a PEAS previously developed by the US National Newborn Screening and Genetics Resource Center, and we report here the development, implementation and results of the Philippine PEAS.
In: Acta Medica Philippina, 2009 vol 43 (2) pages: 58-63
Keywords: Neonatal Screening; PEAS; Performance Evaluation and Assessment Scheme